2020
DOI: 10.1111/tpj.14712
|View full text |Cite
|
Sign up to set email alerts
|

Comparative functional analyses of DWARF14 and KARRIKIN INSENSITIVE 2 in drought adaptation of Arabidopsis thaliana

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 69 publications
3
62
0
Order By: Relevance
“…In the present study, by comparing drought resistance levels of various combinations of knock-out mutants of SMXL6, 7 and 8 genes, including single, double and triple mutants (Figure 1; Figure S1), we firmly showed that SMXL6, 7 and 8 are involved in regulating drought resistance in Arabidopsis plants as redundant negative regulators. Since SMXL6, 7 and 8 are repressors of the SL signaling [6,7], our results provide not only convincing proof for the functions of these three repressors but also an additional evidence to strengthen the positive role of SLs in regulating drought resistance in plants as reported earlier by numerous studies [16][17][18][19][20][21]. For instance, SL-depleted (e.g., max3 and max4) and SL-receptor (e.g., d14) Arabidopsis mutant plants, and SL-depleted L. japonicus (e.g., LjCCD7-silenced) and tomato (e.g., SlCCD7-silenced) transgenic plants were shown to exhibit susceptible phenotypes to various water-deficit stress conditions [16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In the present study, by comparing drought resistance levels of various combinations of knock-out mutants of SMXL6, 7 and 8 genes, including single, double and triple mutants (Figure 1; Figure S1), we firmly showed that SMXL6, 7 and 8 are involved in regulating drought resistance in Arabidopsis plants as redundant negative regulators. Since SMXL6, 7 and 8 are repressors of the SL signaling [6,7], our results provide not only convincing proof for the functions of these three repressors but also an additional evidence to strengthen the positive role of SLs in regulating drought resistance in plants as reported earlier by numerous studies [16][17][18][19][20][21]. For instance, SL-depleted (e.g., max3 and max4) and SL-receptor (e.g., d14) Arabidopsis mutant plants, and SL-depleted L. japonicus (e.g., LjCCD7-silenced) and tomato (e.g., SlCCD7-silenced) transgenic plants were shown to exhibit susceptible phenotypes to various water-deficit stress conditions [16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 86%
“…Thus, the increase in leaf surface temperatures of smxl6,7,8 mutant plants suggests that loss-of-functions of SMXL6, 7 and 8 genes result in enhanced SL signaling, which in turn might promote stomatal closure and consequently drought resistance. Indeed, increasing evidence has indicated the promoting roles of SLs and SL signaling in stomatal closing [15,16,[18][19][20][21]59], further supporting the involvement of SMXL 6, 7 and 8 repressors in regulating stomatal movement through the SL signaling. In addition, various SL-deficient plant species have shown slower stomatal closing rates in the presence of ABA than WT plants [16,20,21], and reduced ABA sensitivity in stomatal response assays, compared with WT [20,21], suggesting the existence of an ABA-dependent mediation of stomatal closure by SLs and SL signaling.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations